A WEBOMETRICS STUDY OF AGRICULTURE UNIVERSITY WEBSITES OF MADHYA PRADESH (LIS TODAY, 2023)
This paper intends to conduct a webometric analysis of the websites of the Agricultural  University of Madhya Pradesh which are managed by the Indian Council of Agricultural  Research (ICAR). The analysis of web link structures is the only area covered. It analyses  three categories of web impact factors: simple, internal, and external, as well as the domain  and page authority. A well-known search engine such as Google has been used for this study's  analysis and measurement of those agricultural repositories' online presence. In this study, we  get that Jawaharlal Nehru Krishi Vishwa Vidyalaya has a well-maintained website structure  such as domain authority, page authority, and several web pages. Nanaji Deshmukh  Veterinary Science University has a well-maintained link structure such as Self-link, Inlink,  and a total number of links.
Keywords: Webometrics analysis; Web Impact Factor; Domain Authority; Domain Authority Page Authority.